Anti-Drug Policies in Iraq Post 2014 (Causes_Effects_Treatments( (قضايا سياسية, 2025)
The study, through its three main axes, aimed to shed light on the underlying factors contributing to the spread of drug abuse in Iraq by addressing the relevant social, security, and economic dimensions. From a social perspective, the study focused on the influence of psychological factors, the role of the family, and peer groups in driving individuals toward drug use. On the security front, it highlighted the repercussions of the 2014 occupation of several Iraqi provinces by terrorist groups, particularly ISIS, and the resulting security vacuum that facilitated the proliferation of drugs. Economically, the study examined how low income levels, rising poverty rates, and unemployment have acted as catalysts for the expansion of drug-related activities, The study also explored the serious social consequences of drug abuse, such as threats to family cohesion and social structure, alongside economic impacts including the spread of financial and administrative corruption, the erosion of the labor force, and the decline in investment opportunities. In terms of security, it emphasized the burden drug-related crimes place on law enforcement agencies, weakening their capacity to address broader security challenges and potentially advancing external agendas. In response to these challenges, the study found that successive Iraqi governments have adopted increasingly stringent public policies to combat drug abuse. These policies are characterized by the criminalization of a wide range of drug-related acts and the imposition of severe penalties on those involved in drug trafficking, with the aim of protecting the community and promoting societal security. In conclusion, after analyzing the causes, consequences, and policy responses, the study reached a set of findings that naturally led to a series of recommendations aimed at curbing the spread of drugs and mitigating their negative effects in Iraq.